The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ejoc.201901565
|View full text |Cite
|
Sign up to set email alerts
|

Domino Hydroalkoxylation‐[4+2]‐Cycloaddition for Stereoselective Synthesis of 1,4‐Heterocycle‐Fused Chromenes: Rapid Access to the [6‐6‐7‐6] Tetracyclic Core of Cytorhizhins B–D

Abstract: A substrate dependent regio‐ and stereoselective domino hydroalkoxylation‐formal‐[4+2] cycloaddition is described for the facile synthesis of linear as well as spirocyclic 1,4‐heterocycle‐fused chromene ketals. Enantiospecific synthesis of oxazepino chromene derivatives was successfully carried out using chiral pool amino alkynols. The developed hydroalkoxylation cascade offered rapid access to the spirocyclic [6‐6‐7‐6] tetracyclic core of cytorhizhins B–D with correct relative configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…More importantly, amino acid‐derived alkynols 36 were used in the transformation for the facile synthesis of enantiopure 2,6‐disubstituted oxazepino chromenes 37 in good to excellent yield and excellent diastereoselectivity (Scheme 15). [55] Only aryl‐substituted alkynes were found to be excellent substrates for the reaction. Further, the presence of electron‐donating and electron‐withdrawing groups on the aryl ring did not affect the cyclization.…”
Section: Carboalkoxylationmentioning
confidence: 99%
“…More importantly, amino acid‐derived alkynols 36 were used in the transformation for the facile synthesis of enantiopure 2,6‐disubstituted oxazepino chromenes 37 in good to excellent yield and excellent diastereoselectivity (Scheme 15). [55] Only aryl‐substituted alkynes were found to be excellent substrates for the reaction. Further, the presence of electron‐donating and electron‐withdrawing groups on the aryl ring did not affect the cyclization.…”
Section: Carboalkoxylationmentioning
confidence: 99%
“…However, in the cases of alkynol 5 k – m , 2 equivalents of TMSOTf was required to complete the reaction. The usage of one more equivalent of Lewis acid could be attributed to the fact that the presence of sulfoxide or sulfone moiety in the alkynols could coordinate with the Lewis acid [10] …”
Section: Figurementioning
confidence: 99%
“…The reaction of various N/O/S-tethered alkynols 34 a-c with salicylaldehyde 28 in presence of 2 equivalents of TMSOTf gave the corresponding 1,4-heterocycle-fused chromenes 35 a-c as a single diastereomer, respectively (Scheme 20). [39] On the other hand, during their substrate scope study, they have observed that, when alkyne is tethered to an aryl ring i. e. o-alkynyl anilines derivatives 36 a-b, instead of linearly fused ketals, spiro-ketals 37 a-b were obtained in good yield and moderate to excellent diastereoselectivity, respectively (Scheme 21). It is pertinent to mention that, the regioselectivity was found to be excellent as in all the cases the spiro-ketals were obtained as the sole product.…”
Section: Acid Promoted/catalyzed Intramolecular Hydroalkoxylation Cascadesmentioning
confidence: 99%